A CASE OF CONCURRENT LUNG CANCER AND FIBROUS-CAVERNOUS PULMONARY TUBERCULOSIS - V. P. Plotnikov; I. V. Perminova; E. E. Chernykh; S. P. Laptev (Туберкулез и болезни лёгких)
The article describes a clinical case of invasive adenocarcinoma and fibrous-cavernous pulmonary tuberculosis For timely diagnosis of lung cancer in those suffering from active respiratory tuberculosis, detail analysis of clinical, laboratory and X-ray data is needed as well as the immediate bronchoscopy examination.